Development as explanation: Understanding phenotypic stability and variability after the failure of genetic determinism. (March 2023) - Moore, David S.; Lickliter, Robert
Abstract: In the predominately gene-centered view of 20th century biology, the relationship between genotype and phenotype was essentially a relationship between cause and effect, between a plan and a product. Abandoning the idea of genes as inherited instructions or blueprints for phenotypes raises the question of how to best account for observed phenotypic stability and variability within and across generations of a population. We argue that the processes responsible for phenotypic stability and the processes responsible for phenotypic variability are one and the same, namely, the dynamics of development. This argument proposes that stability of phenotypic form is found not because of the transmission of genotypes, genetic programs, or the transfer of internal blueprints, but because similar internal and external conditions—collectively conceptualized as resources of development—can be reliably reconstituted in each generation. Variability of phenotypic form, which is an indispensable feature of any evolving system, relies on these same resources, but because the internal and external conditions of development are not reconstituted identically in succeeding generations, these conditions—and the phenotypes to which they give rise—will always be characterized by at least some variability.